Metaphysics and the Method of Ibuanyidanda - Mendie, John Gabriel (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Asouzu's 21st-century philosophy of complementary ontology (popularly known as ibuanyidanda) has brought to bear the abstract nature of metaphysics as expounded by the west. Through the West has a different world view which many African scholars have seen to be driven by anthropocentric tendencies. African system of thought imbibed in communalism have often called for mutual complementarity among whatever that exist, for the essential purpose of attaining the greatest possible flourishing and realizing the common good of man. The Ibuanyidanda philosophy of mutual complementation holds that there is a mutual dependence of all missing links in their unifying interrelatedness. Hence, all cultures, races, sexes, tribes, nations, religions, and political affiliates are in mutual complementary indebtedness to each other in their privileges and responsibilities. The essence of this paper is to a critical look at the position of Ibuanyidanda on metaphysics.